WORK-FAMILY CONFLICT DAN KINERJA GURU WANITA SEKOLAH DASAR NEGERI - HERWANTO HERWANTO; DEWI RUSTINA (Journal of Research and Measurement in Psychology, 2016)
This study was conducted to determine the effect of work-family conflict on the performance of female public elementary school teachers. This study uses quantitative approach, expose facto method. The technique used in this study sample was purposive sampling technique. Researchers adapted teacher performance research instruments developed based on Depdiknas theory. Work-family conflict instruments use the theory of Dawn S. Carlson and Larry J. Williams. The level of teacher performance item reliability of 0.81, and work-family conflict of 0.71. Final respondents from this study as many as 50 people. Hypothesis test is done by using regression analysis. The result of regression analysis showed that the significance value of 0.012 is smaller than the significance level of 0.05, then there is a significant influence of work-family conflict on the performance of female elementary school teachers. The result showed negative effects which indicates that the higher work- family conflict the teacher's performance in this study will decrease. Then the results of this study is a significant difference between work-family conflict on the performance of female public elementary school teachers. The magnitude of the resulting from regression analysis by 12.3%, while 87.7% are influenced by other factors that are not included in this study.